Romanian Art Historiography in the Interwar Period. Between the Search for Scholarship and Commitment to a Cause - Ţoca, Vlad (Artium Quaestiones, 2019)
At the end of World War I, Romania emerged as a much stronger nation, with a greatly enlarged territory. During the two world wars, the Romanian state was permanently looking for the best way to preserve the newly created national state and defend its frontiers. This was the only matter all Romanian parties seemed to agree on. The threat of territorial revisionism coming from Hungary, the Soviet Union and, to a lesser extent, Bulgaria united all the political actors in defending the peace system of Versailles and supporting the League of Nations as the guarantor of this peace and stability. The interwar period was a remarkable time for Romania’s cultural history. Between the two world wars, the Romanian cultural scene was dominated by what Keith Hitchins calls the ‘Great Debate’ about national identity and development. The opponents were those advocating synchronism with the West, on the one hand, and those pleading for tradition, on the other, with many others looking for a third way. In Romanian interwar culture, the country’s modernity was emphasized in order to place the country within the larger family of European nations. An opposing, and at the same time, complementary line of thought was that of presenting the long and noble Romanian history, tradition and ancestral roots. These two themes have been present in Romanian culture since the mid-19th century. They were used by various authors, sometimes in a complementary fashion, while at others, in a conflicting manner in literature, historical writing or political discourse. This process did not end with the creation of the Greater Romania after the end of World War I. New threats, which are mentioned above, maintained the need to continue this discourse. In this context, historical arguments became political arguments and were used by the Romanians in order to justify the new territorial gains and the Versailles system. Art history, part of the family of historical disciplines, came to play an important part in this. Romanian art historical writing or political discourse. This process did not end with the creation of the Greater Romania after the end of World War I. New threats, which are mentioned above, maintained the need to continue this discourse. In this context, historical arguments became political arguments and were used by the Romanians in order to justify the new territorial gains and the Versailles system. Art history, part of the family of historical disciplines, came to play an important part in this. Romanian art historical writing did not exist as such until the end of the 19th century. It was only in the first years of the next century that the number of scholarly works produced following western standards steadily increased. As part of a general tendency of aligning Romanian academic practices with those in the West, art historiography established itself as a respectable academic discipline, a process which went hand in hand with the establishment of new institutions such as museums, university departments, research institutions and the Commission for historical monuments. All these institutions were founded and financed by the Romanian state, and most scholars were involved with these institutions in one way or another. Although Romanian art historiography of the period is dominated by the desire to produce academic works to the highest standards, the ideas of the Great Debate are present in the works of that time. At the same time, in several texts, the most prominent art historians of the day strongly affirm the necessity of putting their work in the service of the national cause. In this paper, we will be looking at the general histories of Romanian art written between the two world wars. The choice of these texts is motivated by the fact that these works are the result of larger research projects and have a broader scope and as such better summarise the trends of the interwar period.